Lanthanoid/Alkali Metal β‐Triketonate Assemblies: A Robust Platform for Efficient NIR Emitters. Issue 50 (29th October 2015) - Reid, Brodie L.; Stagni, Stefano; Malicka, Joanna M.; Cocchi, Massimo; Sobolev, Alexandre N.; Skelton, Brian W.; Moore, Evan G.; Hanan, Garry S.; Ogden, Mark I.; Massi, Massimiliano
Abstract: The reaction of hydrated lanthanoid chlorides with tribenzoylmethane and an alkali metal hydroxide consistently resulted in the crystallization of neutral tetranuclear assemblies with the general formula [Ln(Ae⋅ HOEt)(L )4 ]2 (Ln=Eu 3+, Er 3+, Yb 3+ ; Ae=Na +, K +, Rb + ). Analysis of the crystal structures of these species revealed a coordination geometry that varied from a slightly distorted square antiprism to a slightly distorted triangular dodecahedron, with the specific geometrical shape being dependent on the degree of lattice solvation and identity of the alkali metal. The near‐infrared (NIR)‐emitting assemblies of Yb 3+ and Er 3+ showed remarkably efficient emission, characterized by significantly longer excited‐state lifetimes ( τ obs ≈37–47 μs for Yb 3+ and τ obs ≈4–6 μs for Er 3+ ) when compared with the broader family of lanthanoid β‐diketonate species, even in the case of perfluorination of the ligands. The Eu 3+ assemblies show bright red emission and a luminescence performance ( τ obs ≈0.5 ms, ΦLLn ≈35–37 %, η sens ≈68–70 %) more akin to the β‐diketonate species. The results highlight that the β‐triketonate ligand offers a tunable and facile system for the preparation of efficient NIR emitters without the need for more complicated perfluorination or deuteration synthetic strategies. Abstract : Great excitement! The reaction of hydrated LnCl3, an alkali metal hydroxide, and tribenzoylmethane gives a series of lanthanoid/alkali metal tetranuclear assemblies (Ln=Eu, Er, Yb; Ae=Na, K, Rb). The complexes are emissive in the solid state, and the NIR‐emitting Yb 3+ and Er 3+ species present excited‐state lifetimes that outclass all other species in the β‐diketonate class. This new class of ligands could be a viable alternative to β‐diketonates in light‐emitting technologies.